2021
DOI: 10.1002/jhbp.1012
|View full text |Cite
|
Sign up to set email alerts
|

The optimal timing of interval laparoscopic cholecystectomy following percutaneous cholecystostomy based on pathological findings and the incidence of biliary events

Abstract: Acute cholecystitis (AC) is a common biliary disease. In recent decades, several guidelines, including the Tokyo Guidelines (TG) and World Society of Emergency Surgery (WSES) guidelines, have been established to optimize the management of AC. 1,2 For patients with severe AC or with multiple comorbidities, these guidelines recommend the temporary drainage of bile, that is, percutaneous cholecystostomy (PC), at the acute phase of AC to de-escalate the severity of infection. The safety and efficacy of PC have bee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…In ACC, upfront LC becomes more difficult as fibrosis progresses in the inflammatory process when irrespective of the optimal timing of within 72 h since onset. Fibrosis and adhesions surrounding the gallbladder and in Calot's triangle may be severe in ACC ( 23 ). As a result of increased difficulty for LC to treat ACC, it is absolutely necessary to avoid any increase in bile duct injury, which is the most dreaded complication of LC in ACC with incidence ranging from 0.2% to 7.0% ( 24 ).…”
Section: Discussionmentioning
confidence: 99%
“…In ACC, upfront LC becomes more difficult as fibrosis progresses in the inflammatory process when irrespective of the optimal timing of within 72 h since onset. Fibrosis and adhesions surrounding the gallbladder and in Calot's triangle may be severe in ACC ( 23 ). As a result of increased difficulty for LC to treat ACC, it is absolutely necessary to avoid any increase in bile duct injury, which is the most dreaded complication of LC in ACC with incidence ranging from 0.2% to 7.0% ( 24 ).…”
Section: Discussionmentioning
confidence: 99%
“…The TG18 recommends early surgery for cholecystitis, 1 and several studies have reported the appropriate timing of surgery. [8][9][10][11][12][13][14] These reports compared early cholecystectomy with delayed cholecystectomy in terms of the complication rate, laparotomy conversion rate, hospital stay, and mortality rate, and concluded that surgical removal as early as possible is desirable. These studies have considered and proposed the optimal time frame for surgery, but they did not suggest any basis for the optimal timing of surgery; thus, if early surgery is not possible, the optimal timing for delayed cholecystectomy remains unknown.…”
Section: Discussionmentioning
confidence: 99%
“…The TG18 recommends early surgery for cholecystitis, 1 and several studies have reported the appropriate timing of surgery 8–14 . These reports compared early cholecystectomy with delayed cholecystectomy in terms of the complication rate, laparotomy conversion rate, hospital stay, and mortality rate, and concluded that surgical removal as early as possible is desirable.…”
Section: Discussionmentioning
confidence: 99%
“…Of these, 22 studies reported on outcomes following early interval LC 7,[15][16][17][18][19][20][21][22][23][24][25]36,[43][44][45]47,[49][50][51][52][53] , and 22 studies following late interval LC 3,[25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42]45,46,48 . Three studies reported and compared outcomes in both groups 25,36,45 .…”
Section: Study Characteristicsmentioning
confidence: 99%